A new species for euphorine genus Proclithrophorus (Hymenoptera: Braconidae: Euphorinae) from China - Yu, Haiyue; Peng, Yanqiong; Yao, Junli (Zootaxa, 2025)
A new species of the genus Proclithrophorus Tobias and Belokobylskij, 1981, from Mt Gaoligong National Nature Reserve, Yunnan, SW China: Proclithrophorus gaoligongensis Yao sp. n. is described and illustrated with colorful images which is the first time for the genus. Additional revisional notes on Proclithrophorus are provided as is a key to all three known species of this genus.